Best Answer

x4y3

Answer B

It can be written as x4y3 but it can be switched around such as:

4x3y. This means 4 lots of x's and 3 lots of y's or 4x times 3y.

Ermm I could be wrong.

Q: X x x x y y y simplify this?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

you can't simplify that anymore, you have to know what either x or y equals

(4x + 12)/(8x - 4y) = [4(x) + 4(3)]/(4(2)(x) - 4y] = 4(x + 3)/4(2x - y) = (x+ 3)/(2x - y)

(y * x) - y = y * (x - 1)

3x

x and y are variables, so unless you define their values, this question has no definite answer. but, i can simplify it for you: xy-8, x*y-8, (xy)-8, xy+-8. There are a lot more ways, but i recommend you use XY-8.

Related questions

y2-x2 = (y+x)(y-x)

You can't simplify this any further. y=-x is the equation of a line.

The answer is 5x+3y. (5 xs and 3 ys)

It is y^3/x^2

-2

xy over yx can be simplified to 1. 2x over 2y can be simplified to x over y. So the final step would be to simplify 1 divided by x over y, which would just be 1 multiplied by y over x. Answer: y/x (y over x)

(x + y) / (x-1 + y-1) = (x + y) divided by ( 1/x + 1/y)Multiply numerator and denominator by 'xy' :xy (x + y) / (y + x)Then the whole thing falls apart, and we're left with:xy

I know if you divide by e^(y/x) you get three of the components, but I can't figure out how to get the fraction with the (x+y) as the denominator and where ...

If you are talking about slope/intercept form... you have to remember the formula: y=mx+b Therefore, if you have x+y=4, you need to subtract x from both sides of the equation. x-x+y=-x+4 ... then simplify y=-x+4 Remember that -x is the same as -1x

y/(x+x^2+x^3+x^4+x^5)=.00001001 is the equation. I'd like it to start as "x=". thank you for the help!

I suppose the full question is: Given the following system of equations, find the values of x and y. x+y=2 x+2y=-10 First, you need to isolate the variable y in the equation x+y=2 You do this by subtracting x from both sides of the equation. x+y-x=2-x Simplify: y=2-x Now you substitute the equation 2-x in the place of y in the equation x + 2y=-10 Like this: x+2y=-10 x+2(2-x)=-10 Distribute the two: x+4-2x=-10 Combine like terms: -x+4=-10 Subtract 4 from both sides: -x+4-4=-10-4 Simplify: -x=-14 Divide both sides by negative one to get rid of the negative sign in front of x: -x/-1=-14/-1 Simplify: x=14 Plug the value of x (14) into the equation x+y=2: 14+y=2 Subtract 14 from both sides: 14-14+y=2-14 Simplify: y=-12 Now you are done. From now on, please pay attention in class. If you don't even know the basic math skills that this requires then you have no future.

If Y = y, then it is 9y4 or 9Y4. If Y is not the same as y, then you can't simplify it any.